El dibujo como herramienta de investigación cultural: las casas y sus habitantes - Barrio Juan XXIII - Vélez García, Sara (Educación, Ciencias Humanas y Sociales, 2018)
This work deals with drawing as a tool for social research, as an aesthetic experience that allows the recognition of the houses of the Barrio Juan XXIII of the commune 13, in order to carry out a cultural analysis from the drawing of the neighborhood, which entails to address three key issues; Urban landscape from a cultural aspect, social issues and drawing as an investigative tool. From these 3 themes, pedagogical strategies are proposed from the arts (drawing), to address an analysis of inhabited and inhabited spaces, in order to generate a reflection of aesthetic character with respect to everyday actions that affect the territory. The final reflection allows us to understand the different ways of experiencing our spaces and its construction and of the people who inhabit it, analyze our daily life and how they affect or benefit our habits in the inhabited place. This is approached from the drawing as a research tool. The pedagogical process that can be derived from this experience resembles the methodology used in the process of elaboration of the artistic product of this work, this exercise of recognition of the inhabited place helps to understand the drawing as a tool for understanding, reflection, awareness, analysis and action, through the observation of each aesthetic component of the space drawn